Meningkatkan Kesadaran Dan Pemahaman Mengenai Keamanan Data Pribadi Melalui Kegiatan Sosialisasi Di SMP NEGERI 2 Merawang - Putri, Chaca A.; Melan; Sia Ulgina; Arsanda Lestari; Dimas Firmansyah; Iski Zaliman (Indonesian Journal of Dedication and Educations, 2024)
The development of information technology has brought a significant impact on various aspects of human life, but there are still many internet users who do not realize the importance of protecting their personal data. More than 30% of internet users in Indonesia have not realized the urgency of building privacy data security to prevent unauthorized access. Socialization activities were conducted at SMPN 2 Merawang using participatory methods, discussions, and lectures to increase students' understanding of the importance of maintaining data security, especially in the context of social media. The result of this activity was the dissemination of knowledge about the importance of online privacy and encouraging active participation of participants. It is hoped that this activity can be significant in increasing students' awareness and understanding of the importance of maintaining online privacy and creating a more digitally secure school environment.